Targeting a highly repetitive genomic sequence for sensitive and specific molecular detection of the filarial parasite Mansonella perstans from human blood and mosquitoes. - Nils Pilotte; Tamara Thomas; Michael F Zulch; Allison R Sirois; Corrado Minetti; Lisa J Reimer; Steven A Williams; Lori J Saunders (PLoS Neglected Tropical Diseases)
Background Mansonella perstans is among the most neglected of the neglected tropical diseases and is believed to cause more human infections than any other filarial pathogen in Africa. Based largely upon assumptions of limited infection-associated morbidity, this pathogen remains understudied, and many basic questions pertaining to its pathogenicity, distribution, prevalence, and vector-host relationships remain unanswered. However, in recent years, mounting evidence of the potential for increased Mansonella infection-associated disease has sparked a renewal in research interest. This, in turn, has produced a need for improved diagnostics, capable of providing more accurate pictures of infection prevalence, pathogen distribution, and vector-host interactions. Methodology/principal findings Utilizing a previously described pipeline for the discovery of optimal molecular diagnostic targets, we identified a repetitive DNA sequence, and developed a corresponding assay, which allows for the sensitive and species-specific identification of M. perstans in human blood samples. Testing also demonstrated the ability to utilize this assay for the detection of M. perstans in field-collected mosquito samples. When testing both sample types, our repeat-targeting index assay outperformed a ribosomal sequence-targeting reference assay, facilitating the identification of additional M. perstans-positive samples falsely characterized as "negative" using the less sensitive detection method. Conclusions/significance Through the development of an assay based upon the systematic identification of an optimal DNA target sequence, our novel diagnostic assay will provide programmatic efforts with a sensitive and specific testing platform that is capable of accurately mapping M. perstans infection and determining prevalence. Furthermore, with the added ability to identify the presence of M. perstans in mosquito samples, this assay will help to define our knowledge of the relationships that exist between this pathogen and the various geographically relevant mosquito species, which have been surmised to represent potential secondary vectors under certain conditions. Detection of M. perstans in mosquitoes will also demonstrate proof-of-concept for the mosquito-based monitoring of filarial pathogens not vectored primarily by mosquitoes, an approach expanding opportunities for integrated surveillance.